The fifth discipline the art and practice of the learning organization - Senge, Peter M. 1947- (Business Management, 2006)
"In The Fifth Discipline, Peter Senge describes how companies can rid themselves of the learning "disabilities" that threaten their productivity and success by adopting the strategies of learning organizations - ones in which new and expansive patterns of thinking are nurtured, collective aspiration is set free, and people are continually learning how to create results they truly desire." "The revised and updated Currency edition of this business classic contains over one hundred pages of new material based on interviews with dozens of practitioners at companies like BP, Unilever, Intel, Ford, HP, Saudi Aramco, and organizations like Roca, Oxfam, and The World Bank. It features a new Foreword about the success Peter Senge has achieved with learning organizations since the book's inception, as well as new chapters on Impetus (getting started), Strategies, Leaders' New Work, Systems Citizens, and Frontiers for the Future."--BOOK JACKET.